2002
DOI: 10.1111/1467-8535.00269
|View full text |Cite
|
Sign up to set email alerts
|

The word processor re–visited: observations on the use of the word processor to develop literacy at key stage 2

Abstract: Background to the studyThe word processor has been present in schools for over twenty years and has longed seemed an ideal tool to encourage pupils to re draft text as well as offering other advantages such as a shared screen for collaborative working and professional presentation of writing. Not surprisingly some case studies have provided valuable evidence on the value of word processor for young writers ( eg, Dauite, 1985;Dalton and Hannafin, 1987;Breese, Jackson and Prince, 1996).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
5

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 1 publication
0
8
0
5
Order By: Relevance
“…In the case of the English curriculum, Mumtaz and Hammond (2002), found that wordprocessing was not fully embedded and that often word-processing was used superficially with pupils with little opportunities for drafting and redrafting through which the most positive effects have been identified. Similar evidence of limitations to curriculum integration was found for the use of ICT in science when teachers were studied using computer based modelling (Mellar et al 1994).…”
Section: The Problem About the Different Effects Of Specific Types Ofmentioning
confidence: 99%
“…In the case of the English curriculum, Mumtaz and Hammond (2002), found that wordprocessing was not fully embedded and that often word-processing was used superficially with pupils with little opportunities for drafting and redrafting through which the most positive effects have been identified. Similar evidence of limitations to curriculum integration was found for the use of ICT in science when teachers were studied using computer based modelling (Mellar et al 1994).…”
Section: The Problem About the Different Effects Of Specific Types Ofmentioning
confidence: 99%
“…In the case of English, it may be the case that what the pupils did on the computer (for example copytyping in order to improve the presentation of work, or using the Internet for unsupervised research, to quote two examples from our case studies, Becta, 2002b, c) simply had little or no pay-off in terms of the skills and knowledge tested in the examinations (this analysis would also be supported by the findings of Mumtaz and Hammond, 2002). This would contrast greatly with the Bytesize revision material for Science, for example, in which the programme content not only helped to explain or exemplify difficult concepts that were highly relevant for the examination, but also presented pupils with mini-tests that were similar in form and content to those that would be met under examination conditions.…”
Section: Discussionmentioning
confidence: 69%
“…Teachers who base their use of ICT on its vocational value may see the teaching, or at least the learning of ICT skills, as an end in itself (eg, Drenoyianni & Selwood, ). For example, the widespread reported practice of leaving children to use word processors for solely presentational purposes (eg, Mumtaz & Hammond, ) is not aligned to any viable view of teaching writing skills, but can be justified by the acquisition of ICT skills. The problem of distortion is long standing.…”
Section: A Distorted View Of Technology In the Curriculummentioning
confidence: 99%